Association of thyroid function with insulin resistance: data from two population-based studies. Issue 2 (28th February 2022) - Spira, Dominik; Buchmann, Nikolaus; Dörr, Marcus; Markus, Marcello R P; Nauck, Matthias; Schipf, Sabine; Spranger, Joachim; Demuth, Ilja; Steinhagen-Thiessen, Elisabeth; Völzke, Henry; Ittermann, Till
Abstract : Objective: Thyroid dysfunction is associated with relevant disturbances in glucose metabolism. Moreover, thyroid function undergoes important changes with ageing. The objective of this study was to investigate the association of thyroid function with insulin resistance with particular consideration of possible age-related effect modifications. Design: A sample of 4193 participants from two independent epidemiological studies, the Study of Health in Pomerania-TREND-0 and the Berlin Aging Study II, was included in this cross-sectional analysis. Methods: Insulin resistance was estimated by homeostasis model of insulin resistance (HOMA-IR) and the insulin sensitivity index (ISI). Associations of thyroid biomarkers (thyroid-stimulating hormone, free thyroxine, and free triiodothyronine (fT3)) with parameters of glucose metabolism were analysed by regression models adjusted for age, sex, smoking status, and study site. Results: A higher fT3 was significantly associated with higher fasting glucose and higher fasting and 2-h postload insulin levels, a higher HOMA-IR, and lower ISI. A higher fT3 was also associated with a higher risk for impaired fasting glucose (RR 1.09, 95 CI 1.02; 1.18; P   = 0.017). Many of these associations between thyroid markers and parameters of glucose metabolism were significant in young and middle-aged participants but not in older individuals. Conclusions: The main finding of this study was a consistent association of fT3 with almost all markers of insulin resistance. However, this effect seems to be wearing off in higher age highlighting a potential age-related modification of the interaction between thyroid function and glucose metabolism. Further studies are needed to clarify causal relationships.